Potential for sharing of common regional resources in the Eastern Himalayan Region : focus on Sapta Kosi High Dam Project - Ahmad, Qazi Kholiquzzaman, 1943- (Bangladesh Unnayan Parishad, 2004)
With reference to the Project area in India, Bangladesh, and Nepal.